Internalisasi Nilai Islam Wasathiyah, Pancasila dan Kewarganegaraan dalam Membangun Karakter Mahasiswa Pendekatan Model Value Learning - Sri Hudiarini (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
This research is a qualitative descriptive study intended to describe and describe existing phenomena, both natural and human engineering, which pay more attention to characteristics, quality, and related to ongoing events and related to current conditions. Pancasila and Citizenship Education aims to build the character (character building) of the Indonesian nation, citizen participatory skills, and responsibility in the nation and state's life. To achieve this goal, it is necessary to have the proper selection of the learning model used and in research conducted on students at the State Polytechnic of Malang. Keywords: Islam Wasathiyah, Pancasila, Citizenship, Character, Value Learning Model